A mouse pancreatic organoid model to compare PD-L1 blocking antibodies. Issue 1 (31st December 2022) - Li, Guangyuan; Ghosh, Susmita; Park, JuMe; Shin, Hyunsu; Garige, Mamatha; Reaman, Gregory; Sourbier, Carole
ABSTRACT: Immune checkpoint inhibitors (ICIs) have changed the therapeutic landscape for cancer patients, but diabetes, a rare, severe immune-related endocrinopathy, is linked to ICI therapy. It is unclear whether glycosylation of ICIs may play a role in the development of this adverse event and how the physiological effects of different ICIs on pancreatic cells should be evaluated. We used a mouse pancreatic organoid model to compare three PD-L1 blocking antibodies in the presence or absence of IFNγ using a metabolic bioanalyzer. Modulation of ICI glycosylation altered its metabolic effects on mouse pancreatic organoids, suggesting that this model could be used to monitor and compare ICIs and to study the mechanisms underlying the development of IC-mediated diabetes.